LEARNING USING ANIMATED VIDEOS FOR PRIMARY SCHOOL STUDENTS - _, Meilisna; _, Misnah; Ratu, Bau; _, Iskandar; _, Nurwahyuni; Elfira, Ninil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2024)
The educational curriculum and the digital era require teachers to be more creative and innovative in selecting and sorting learning media that can attract students to learn. It can be said that the world of technology has become a special attraction for students, especially in the world of education. This research aims to describe animated video learning media for students in elementary schools. The research method used is descriptive qualitative, where research begins with an understanding of the phenomenon and then describes it through words. Animated video learning media can improve student learning outcomes and is highly recommended for teachers teaching in elementary schools.